KONFLIK NELAYAN DI KECAMATAN LINGGO SARI BAGANTI DAN PANCUNG SOAL KABUPATEN PESISIR SELATAN (Studi Kasus : Air Haji dan Pulau Rajo Inderapura Tahun 1998-2010) - PURNIATI, NINA - (Pendidikan Sejarah, 2014)
This research is analyzing the conlicts between Linggo Sari region and Pancung Soal region in the Pesisir Selatan regence (case of study is : Air Haji Tanjung Kandis And Pulau Rajo Inderapura at 1998th until 2010th). The indications problem of this research are : how the background of conflict between fisherman of Nagari Air Haji Tanjung Kandis And Pulau Rajo Inderapura at 1998th-2010th and also how to the solutions of this conlict.The method of this research are historical mothod that devided in four step : The first is heuristic step, heuristic is colecting the data from old document, the other document, any relevant book and discussing.The second step criticts the data, criticts the data is procesing the data, sourches and information to know the originally . The next step is interpretations, interpretations is interprating the originally data to get the right informations for the right informing in served the data.The Last Step is historiograf, historigraf is serving the data in the academicalÂ writing (skripsi).As the result of this research is describing that this conflict base on the differentiation of the tool to take the fish that is used by fisherman and the social gelouse of one group of fisherman and other about the different of theirs result.